PENGARUH LITERASI KEUANGAN TERHADAP KEBERLANGSUNGAN UMKM DI SEMARANG - Eviyanti, Novitasari; Raharjanti, Rani; Asrori, Muhammad; Haris, M.; Murtiasri, Eka (Politeknik Negeri Semarang, 2024)
In Indonesia, there are many MSMEs that don't know much about Financial Literacy, so many have difficulty getting capital and end up going bankrupt. This research uses quantitative methods with descriptive research type. Sampling was carried out using a non-probability sampling method, saturated sampling type, with the number of respondents studied being 37 MSMEs. Based on a simple linear test by testing the hypothesis, financial literacy influences the sustainability of MSMEs. This is shown by the t table test result = 2.305 and the calculated t result is 5.825. So the calculated t is greater than the t table (5.825 > 2.305) which means that financial literacy has a significant effect on business sustainability.